Unusual presentation of duplex kidney with poor functioning upper moiety in an adult patient a case repor - Hina Khalid; Naveed Ahmed Mahar; Murli Lal (Archive of Urological Research - Peertechz Publications, 2022)
Renal duplexing (also known as a duplicate collection system) occurs in about 1% of children and does not usually require medical attention. The condition results in two tubes rather than the normal single ureter tube for each kidney. Medical problems that warrant attention are obstruction of urine flow or the backflow of urine into the kidney (reflux). These double ureter tubes can join in a "y" shape before reaching the bladder (partial duplex) and combining their urine delivery. In other cases, each duplicate ureter empties into the bladder on its own (complete duplex). There is cause for concern when a duplex kidney is associated with urological conditions requiring treatment. Renal duplexing can cause urine to reflux into the kidney (vesicoureteral reflux) rather than going into the bladder and can cause subsequent Urinary Tract Infection (UTI). This can result in serious consequences like the loss of renal parenchyma (reflux nephropathy) and sometimes death in acute infections if not attended to in a timely manner. Weigert-Meyer postulated that rule i-e in a complete duplex system is mostly associated with reflux in lower moiety and obstruction in upper moiety with ectopic insertion and ureterocele. Ureteroceles may require simple management of symptoms or surgery, depending on the size of the ballooning, the functioning of the kidney and bladder and the degree of urine obstruction. An ectopic ureter is when the ureter opens and drains urine outside the bladder rather than inside.